Uji adaptasi varietas unggul dan galur harapan padi umur sangat genjah pada musim kemarau dan musim hujan di kabupaten Sragen, Jawa Tengah - Toto Suhendrata (Jurnal Ilmu Pertanian Indonesia, 2010)
The study was carried out in the Village Gondang, Sragen Regency Central Java in the dry season (JuneOctober 2009) and in the wet season (October 2009 -January 2010). The design of the study using a randomized block design with six replication. Treatments consisted of two rice varieties and three rice elite lines very short maturity i.e. varieties Silugonggo, Inpari 1 and rice elite lines OM 1490, OM 2395 and 811283. The results of the study indicated that (i) harvesting of OM 1490 and OM 2395 in the wet season were shortern than harvest age in the dry season, while harvesting a variety Silugonggo and Inpari 1 in the wet season were longer than the harvesting in the dry season, (ii) Silugonggo, Inpari 1 , OM 1490, OM 2395 and 811283 adaptive and productive planted in the irrigated lowland, especially in the dry and wet seasons. Productivity in the dry and in the wet seasons were Inpari 1 (9.2 and 8.4 t/ha), Silugonggo (9.3 and 8.2 t/ha), OM 1490 (9.5 and 8.1 t/ha), OM 2395 (8.9 and 7.7 t/ha) and 811283 in the wet season (8.1 t/ha) dried grain, (iii) productivity in the dry season were higher than in the wet season. The average productivity was different between that in the dry and in the wet season were Silugonggo 1.1 t/ha, Inpari 1 0.8 t/ha, OM 1490 1.4 t/ha, and OM 2395 1.2 t/ha dried grain or decreased of productivity between 8.70 -14.74%, and (iv) Inpari 1 and OM 1490 more preferred of the farmers compared Silugonggo and OM 2395.